2016
DOI: 10.5993/ajhb.40.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Substance Use among US Adolescents, 1991-2014

Abstract: Objectives To examine associations between sleep and alcohol, amphetamine, cigarette, marijuana, and non-heroin narcotic use among US middle and high school students, trends in associations over time, and the comparative impact of select covariates on association strength. Methods Data from the 1991–2014 nationally representative Monitoring the Future study of 8th, 10th, and 12th grade US students were used to estimate standardized correlations between the frequency of getting at least 7 hours of sleep (7+ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…A likely pathway for this connection is that lack of sleep is known to diminish teens' executive cognitive functioning and emotional regulation. 3 In the area of substance use, a recent analysis from the cross-sectional Monitoring the Future study demonstrated that the frequency of obtaining 7 or more hours of sleep per night was associated with a reduced risk of using cigarettes, alcohol, marijuana, and amphetamines, 4 which echoes other cross-sectional reports on sleep deficiencies and substance use. [5][6][7][8][9] With regard to mental well-being, shorter sleep duration among adolescents is associated with lower self-esteem, 10 a more negative attitude toward life, 11 greater difficulty with emotional regulation, 12 higher rates of mood disorders, 8,9,[13][14][15][16] and more thoughts of suicide.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A likely pathway for this connection is that lack of sleep is known to diminish teens' executive cognitive functioning and emotional regulation. 3 In the area of substance use, a recent analysis from the cross-sectional Monitoring the Future study demonstrated that the frequency of obtaining 7 or more hours of sleep per night was associated with a reduced risk of using cigarettes, alcohol, marijuana, and amphetamines, 4 which echoes other cross-sectional reports on sleep deficiencies and substance use. [5][6][7][8][9] With regard to mental well-being, shorter sleep duration among adolescents is associated with lower self-esteem, 10 a more negative attitude toward life, 11 greater difficulty with emotional regulation, 12 higher rates of mood disorders, 8,9,[13][14][15][16] and more thoughts of suicide.…”
Section: Introductionmentioning
confidence: 77%
“…12,38 Prior research on sleep and tobacco use in teens have discovered similar findings. 3,4 Sleep deprivation of less than 8 hours per night and sleeping longer than is considered normal at 9.25 hours for adolescents are similar in that both can be viewed as likely being symptomatic of other environmental and emotional issues that preclude or induce sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of combustible cigarette use on sleep has been well established. Cigarette use has been associated with poor sleep health in national samples of adolescents (Terry‐McElrath, Maslowsky, O'Malley, Schulenberg, & Johnston, ) and adults (McNamara et al., ; Sabanayagam & Shankar, ), including college students (Boehm, Lei, Lloyd, & Prichard, ). A population‐based case–control study using the Pittsburgh Sleep Quality Index (PSQI; Buysse, Reynolds, Monk, Berman, & Kupfer, ) found significant differences in global sleep score between smokers and non‐smokers, with current smokers exhibiting more sleep disturbance (Cohrs et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several longitudinal studies have linked sleep disturbance during adolescence with tobacco use (Bellatorre et al 2017; Warren et al 2017) and alcohol use (Miller et al 2017; Nguyen-Louie et al 2017; Sivertsen et al 2015). Additionally, eveningness (a preference for later sleep-wake timing) (Hasler et al 2017, 2015), and short sleep times (Terry-McElrath et al 2016) have also been identified as risk factors for alcohol and/or marijuana use in adolescents.…”
Section: Introductionmentioning
confidence: 99%